Development of automatic manipulators for plastic injection machines - Penne, Robin (2021)
The automotive industry is a competitive sector, always asking for improvements in productivity, efficiency and quality. This is the reason why the demand for automation of processes arises, resulting in relying less on manpower. Bowden cables are mechanical elements that allow the transmission of motion between two or more systems. They are most of the time not visible for the user. Some examples of applications inside the car are opening doors, windows, seat’s adjustment, among many others. At present, the production of Bowden cables is done by multiple working stations with multiple operators. This work is focused on the workstation where the end of the conduit is injected. At the moment, there are injection machines with a capacity of 8 conduits at the same time and one operator at every injection machine. These injection machines need a lot of space, spend a lot of energy and usually present persistent breakdown problems, needing maintenance. The future outlook of the company is, to have smaller injection machines with a capacity of 4 conduits at a time and one operator for 2 injection machines. These injection machines are easier in maintenance and also occupy less space, consuming less energy as well. The main goal for this project is to make it possible to have 1 operator at 2 injection machines. The possibility to fully automate was rejected as it is really hard to automate the feeding of the conduits in the injection machines due to low stiffness of the conduits, becoming hard to align them in the mould. The proposed solution to make this happens is to design a manipulator to take out the 4 conduits and the scrap out of the mould. The scrap and the conduits then need to be separated, scrap to a recycling box and the conduits to a production/supply chain box. The manipulator has been successfully designed, after a thorough comparison of a variety of possibilities. All the components that were needed for this concept have successfully been defined, calculated, selected and integrated into the design. After the designing process, a budget and payback calculation has been done, as well as a return of investment. Lastly, a maintenance manual and an assembly manual has been elaborated in order to ease the assembly of all the components. The results after implementing the designed solutions are a reduction in energy consumption of the injection peocess (79,8%) and an improvement in productivity (12,0%).